2021
DOI: 10.1155/2021/3582989
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics as a New Regulator for Bone Health: A Systematic Review and Meta-Analysis

Abstract: Despite the proposed role of the gut microbiota-bone axis, findings on the association between probiotic consumption and bone health are conflicting. This systematic review aimed to assess the effect of probiotic consumption on bone health parameters. A systematic literature search of relevant reports published in PubMed/Medline, Web of Science, SCOPUS, EMBASE, and Google scholar before December 2020 was conducted. All clinical trials or experimental studies, which examined the relationship between probiotic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 85 publications
2
8
0
1
Order By: Relevance
“…[174][175][176]. Similar results are reported by other RCTs [168,170,172,173]. If diet-induced weight loss is combined with exercise training, there is an attenuation of the loss of total hip BMD in older obese patients [168,169,173].…”
Section: Effect Of Weight Losssupporting
confidence: 81%
See 1 more Smart Citation
“…[174][175][176]. Similar results are reported by other RCTs [168,170,172,173]. If diet-induced weight loss is combined with exercise training, there is an attenuation of the loss of total hip BMD in older obese patients [168,169,173].…”
Section: Effect Of Weight Losssupporting
confidence: 81%
“…Gut microbiota (GM) dysbiosis has been identified in various diseases, such as hypertension, Alzheimer disease, type 2 diabetes, depression, and also in obesity [164][165][166][167][168][169]. Several studies have also shown a relationship of GM dysbiosis with bone health [170]. It can be inferred that the relationship between obesity and bone can also be conditioned by GM.…”
Section: Gut Microbiotamentioning
confidence: 99%
“…Several hypotheses could be explored to characterize the origin of this L. helveticus VEL12193-related phenotype. The firstone would be a loss of muscle and/or bone mass, but such an hypothesis is unlikely since lactobacilli have been shown to instead have the opposite effect [37][38][39][40] . A second possibility would be a modulation by L. helveticus VEL12193 of the gut microbiota capacities on nutrient absorption, energy expenditure and/or fat oxidation 41,42 .…”
Section: Discussionmentioning
confidence: 99%
“…Further, the strong and dose-dependent anti-inflammatory properties of L. acidophilus spp. has been reported [122][123][124][125][126] , where combined probiotics showed the most efficacious antiinflammatory activity, [121,127] potentially via NF-𝜅B signaling. [128] Lipopolysaccharide stimulates the synthesis of substantial levels of NO, ROS, and cyclooxygenase-2 (COX-2) in macrophages resulting in cellular oxidative stress, [129][130][131] and DNA damage.…”
Section: Discussionmentioning
confidence: 99%